Culture, Spatial Diffusion of Ideas and their Long-Lasting Imprints - Evidence from Froebel's Kindergarten Movement - Stefan Bauernschuster; Oliver Falck (Center for Economic Studies and ifo Institute (CESifo), 2014)
We document the spatial diffusion of Friedrich Froebel's radical invention of kindergartens in 19th-century Germany. The first kindergarten was founded at Froebel's birthplace. Early spatial diffusion can be explained by cultural proximity, measured by historical dialect similarity, to Froebel's birthplace. This result is robust to the inclusion of higher order polynomials in geographic distance and similarity measures with respect to industry, geography or religion. Our findings suggest that a common cultural basis facilitates the spill-over of ideas. We further show that the contemporaneous spatial pattern of child care coverage is still correlated with cultural similarity to Froebel's place of birth.
Keywords: N33; J13; Z13; 330; culture; spatial diffusion; public child care